High performance liquid chromatographic determination of Mefenamic acid in human plasma using UV vis detector - Helal Uddin, A.B.M.; Mohamad, Huda Jamilah; Alaama, Mohammed; Amiruddin, Noor Syafawati (2014)
Mefenamic Acid (MA) is a non-steroidal anti-inflammatory drug (NSAIDs). It is a class of drug that provides analgesic and antipyretic (fever reducing effect) and in higher doses, anti-inflammatory effect. This study is focused to develop a rapid and sensitive method for the detection of mefenamic acid in human plasma. A simple and sensitive high-performance liquid chromatography-UV detection method was developed for the detection of mefenamic acid. Protein precipitation technique using acetonitrile was used. Chromatographic separation was achieved on Agilent Zorbax Eclipse XDB-C18 (150 mm x 4.6 mm, i.d 3.5µm) with a mobile phase consisting of acetonitrile and 2% triethylamine (pH was adjusted to 4.2 with phosphoric acid) in a ratio of 60:40. The retention time for mefenamic acid and diclofenac was 5.4 and 3.9 minutes respectively. The mefenamic acid was monitored under 280 nm using variable-wavelength detector. The recovery was found to be 83% for MA. The method was validated for following the CDER (Centre for Drug Evaluation and Research) guideline. Calibration plot were linear within the range from 250 to 5000ng ml-1 with the correlation coefficient (r2) of ≥ 0.99. The result from analysis of quality control of mefenamic acid which were termed as low, medium and high were analysed to get the precision and accuracy. The accuracy for intra-day for low, medium and high were 99.71%, 93.8% and 89.52% while for inter day were 97.67%, 93.46% and 91.67% respectively. On the other hand, coefficient of variance (CV) for intra-day precision for low, medium and high were found 2.57%, 2.45% and 1.45% and for inter day CV were 3.11%, 5.5% and 4.37% respectively. Diclofenac sodium was used as internal standard for this study.